Effect of Photoinitiator Type and Photoactivation Condition on the Physical-Mechanical Properties of Orthodontic Resins - Roseira, Priscila Maito; Gomes, Camila de Siqueira; Topolski, Francielle; Gonzaga, Carla Castiglia; Moro, Alexandre; Alonso, Roberta Caroline Bruschi; Nolasco, Gisele Maria Correr (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Purpose: The aim of this study was to evaluate the physical-mechanical properties of experimental orthodontic resins, containing different photoinitiators systems and photoactivated through a ceramic bracket, using a high irradiance and wide spectrum light emitting diode curing unit. Methods: Experimental resin composites (50:50 BisGMA/TEGDMA: 60% feldspar silanized particles) were formulated with different photoinitiators according to the following groups: phenylpropaneamine + amine DMAEMA (PPD), camphorquinone + amine DMAEMA (CQ) or bisacylphosphinic oxide (BAPO). A commercial orthodontic resin composite (Transbond XT) was used as control. The materials were then distributed into two groups, according to the photoactivation condition: directly or through a ceramic bracket, for 20s at 1200 mW/cm2. In the sequence, fifteen composite disks, 5mm of diameter and 1mm of thickness, were made for each of the eight groups. The degree of conversion (DC) was determined by means of Raman spectroscopy. Knoop hardness (KHN) was measured immediately after confection and after 24 hours of storage in 100% ethanol for indirect crosslink density (CLD) evaluation. Data were analyzed using two-way ANOVA followed by Tukey's test (α = 0.05). Results: The DC of the BAPO composite was significantly higher in comparison to the other materials, regardless of the photoactivation condition. The KHN was significantly different between the composite groups in the following sequence: BAPO> Transbond XT> CQ> PPD. The direct photoactivation presented higher KHN values, regardless the type of material. Regarding the CLD, there was statistical difference only for the material factor, as follow: PPD> BAPO = CQ = Transbond XT. Conclusion: The photoinitiator type and the photoactivation condition had a significant influence on the physical-mechanical properties of the evaluated materials.